Effect of chronic morphine treatment on transmitter release from sympathetic varicosities of the mouse vas deferens. - Lavidis, N. A. (1995)
1 Transmitter release from sympathetic varicosities of mouse vasa deferentia removed from animals which were chronically treated with morphine for 7 to 9 days has been evaluated. 2 In control preparations increasing the extracellular calcium concentration ([Ca2+]o) from 1 to 2 mM increased transmitter release by 3 fold while increasing [Ca2+]o from 6 to 8 mM increased transmitter release by about 0.9 fold. Introduction of morphine (1.0 microM) produced a uniform decrease in transmitter release, shifting the relationship between transmitter release and [Ca2+]o to the right. 3 Only sympathetic varicosities with probabilities of transmitter release greater than 0.01 were chosen for this study. In these varicosities the decrease in transmitter release induced by morphine in control preparations (bathed in [Ca2+]o 2.0 mM) was not observed following 7 to 9 days of morphine treatment. When the morphine was acutely withdrawn from these preparations transmitter release was more than 6 times the average level of transmitter release from control preparations. 4 The morphine induced increase in facilitation of transmitter release while stimulating with short trains of nerve impulses was not observed when the preparations were removed from animals which had been exposed to morphine for 7 to 9 days. When these preparations were acutely withdrawn from morphine there was a further decrease in the level of facilitation and a significant increase in depression of transmitter release when compared to control. 5 The morphine induced decrease in probability of transmitter release when naive sympathetic varicosities in vitro were bathed with morphine (1 microM) was not observed following chronic morphine treatment of the animals for 7 to 9 days. When the morphine was acutely withdrawn from chronically morphine treated preparations the underlying increase in probabilities of transmitter release of sympathetic varicosities was unmasked.